Metal poisoning and the most important ways to prevent it - Amir Ayed Muhaibas Obaid; Omama Mohammed Salman Mahmoud; Sabah Takleef obald Hassan; Ahmed Majid Abdul Hamid (Genius Journals, 2024)
In this research, we reviewed the effects of some heavy metals, such as arsenic, lead, mercury, cadmium, and aluminum, on the environment and living organisms, especially humans. It is essential to have effective legislation and guidelines and detect areas with higher levels of heavy metals. Failure to control exposure will lead to serious complications in the future due to the harmful effects imposed by heavy metals. Occupational exposure to heavy metals can be reduced through engineering solutions. Exposure monitoring and potential intervention to reduce additional exposure to heavy metals in the environment and humans can become a critical step towards prevention. National and international cooperation is vital and appropriate to prevent heavy metal toxicity
Keywords: heavy metals; lead; mercury; cadmium